Anti-corruption Law and Systemic Corruption: The Role of Direct Responses - Kevin E. Davis (Revista Direito GV)
Abstract Recent discussions of systemic corruption have cast doubt on the effectiveness of direct legal responses, that is to say, responses that involve the enforcement of explicit legal prohibitions on corrupt activity. This article argues that there are sound reasons to believe that anti-corruption law can play an affirmative role in controlling systemic corruption, but the advantages and disadvantages of alternative legal responses are likely to vary depending on both the preferred evaluative criteria and the context. This analysis is based on the premise that corruption becomes systemic when it is widespread, persistent, subversive, structural, or normalized. There are three general ways in which law enforcement agencies might respond to these forms of corruption: an enhanced effort (“big push enforcement”), get more agencies involved (“institutional multiplicity”), and win over the general public by confront powerful actors using tactics such as communication strategies (“political engagement”). Although each of these responses has limitations and dangers, they also have potential advantages. Thus, to entirely dismiss direct legal responses to systemic corruption appears to be a misguided response.